1995 Special Issue - Abdel Wahab Elmesseri (International Institute of Islamic Thought, 1994)
The definition of secularism as the separation of church and state has gained currency and has become more or less universally accepted, probably because of its tameness. It confines the secularizing processes to the political and economic realms. Although it could be extended to cover what is commonly called the realm of "public life," it never goes beyond that. The term suggests that processes of secularization are explicit and quite identifiable, and that an individual's private life (i.e., dreams and nightmares, tastes and aesthetic sensibilities) can be hermetically sealed off and thus remain free of the ravages of secularism. One glance at life in the modern West demonstrates the fallacy of this assumption. The state, far from staying out of the realm of public life, has penetrated deeper and deeper and into to the farthest comers of our private lives. The corporations and pleasure industries have infiltrated our dreams, have shaped our images of ourselves, and have controlled the very direction of our libidos. Like most, or probably all, world outlooks, secularism revolves around three elements: God, humanity, and nature (nature is hereafter referred to as "nature-matter" in order to emphasize the philosophical dimension of the concept and to dispel the romantic aura that has surrounded it and weakened its analytical and explanatory power). The attitude of God-is He transcendent or immanent; is He above nature and humanity and history or immanent in (namely reducible to) them-is what defines the status of a human being in the universe and hisher relationship to nature-matter. Secularism declares that it is immaterial whether or not God exists, for He has very little to do with the formulation of our epistemological, ethical, aesthetic, and signifying systems. If God exists, He takes two extreme forms: a) He could be too transcendent and removed from humanity and nature, indifferent to human suffering, or b) He could be seen as completely immanent in both humanity and nature (or in either) and as having no existence separate from them. This view, which is the more common of the two, is known as immanence. Immanence implies that a) the world as given has within it all that is necessary for its full understanding and utilization, and b) that the human mind is so equipped that it could acquire all of the knowledge necessary for a full understanding of, and dominance over, nature. If nature is autonomous and self-sufficient, then so is the human mind. This duality (or dualism) produced two orientations within the same secular outlook: ...